If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6x + 7 = x + -5 + 12 Reorder the terms: 7 + 4x + -6x = x + -5 + 12 Combine like terms: 4x + -6x = -2x 7 + -2x = x + -5 + 12 Reorder the terms: 7 + -2x = -5 + 12 + x Combine like terms: -5 + 12 = 7 7 + -2x = 7 + x Add '-7' to each side of the equation. 7 + -7 + -2x = 7 + -7 + x Combine like terms: 7 + -7 = 0 0 + -2x = 7 + -7 + x -2x = 7 + -7 + x Combine like terms: 7 + -7 = 0 -2x = 0 + x -2x = x Solving -2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2x + -1x = x + -1x Combine like terms: -2x + -1x = -3x -3x = x + -1x Combine like terms: x + -1x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| 12-2y=10y-12 | | 8a-11=4a+13 | | (13/15)-(d/5)=(5/6)+(d/3) | | 37x-93=82+32x | | 7x+2=-7x+142 | | x^2-1x-2=0 | | 49x^2-70xy+25y^2= | | 3+2x+4x=-33 | | 7+7x+4x=106 | | -2(1-4x)=8x-2 | | 10x-2-2x=4 | | 2(x-1)+7=4x+3 | | 8-2x+5x=32 | | 2X+3=4(X+1) | | 12h=9ht+84 | | -9p+-17=10 | | 27-4n=35 | | x-9-3x=-33 | | 12x+24=97+8x | | 58=6(1-3x)-8x | | 144x^2-1= | | 384c^2-150=0 | | -4x+37=-3(1+4x) | | -4x+10-x=70 | | 8-6x=62 | | 3+2x+45+6x=303 | | 9r^2-64=0 | | 17x-130=280+7x | | y^3-13y^2+30y=0 | | p=-2 | | 9-4x=-3 | | 5a^2-an-22b^2=0 |